Molluscicide baits impair the life traits of Folsomia candida (Collembola): Possible hazard to the population level and soil function - Cardoso, Diogo N.; Santos, Miguel J.G.; Soares, Amadeu M.V.M.; Loureiro, Susana (Chemosphere (Oxford), 2015)
[Display omitted] •Molluscicide baits attracted collembolans.•Collembolans reproduction and survival were adversely affected by molluscicide baits.•One bait pulse exposure increased toxicity when compared to a single bait exposure.•Molluscicidal baits can harm collembolans in realistic exposure scenarios. The application of molluscicides baits on the soil surface is the most common practice to control terrestrial gastropods. There seems to be a gap in the accurate evaluation of molluscicidal baits effects to soil arthropods, since their hazard to non-target organisms has been considered low after mixing baits into soil. In this work the ecotoxicological effects of two molluscicide baits (metaldehyde and methiocarb) to the collembolan Folsomia candida were evaluated using two different approaches: (1) molluscicidal baits were applied to the top soil once and only at the beginning of the exposure and avoidance behaviour and reproduction were evaluated; and (2) baits were replaced by new ones after 14-d of exposure, simulating the recommended application rate recommended by the manufacturer and reproduction was assessed (repeated/pulse exposure). A preference for the side contaminated for methiocarb was observed but the distribution of collembolans in the avoidance test with metaldehyde was random. Exposure to metaldehyde resulted in a significant increase in mortality. For methiocarb, a reduction in the juveniles produced but no acute effects were observed. In the bait pulse test, the toxic effects of each chemical was significantly increased compared with the single exposure test, for all treatments used (both reproduction and mortality). In summary, molluscicides have an adverse effect on F. candida, with severe effects on their behaviour (only for methiocarb), reproduction and survival (for both), which can lead to population collapse with time.